EFEKTIVITAS PROGRAM PELATIHAN KETERAMPILAN BAGI PENYANDANG CACAT TUNA RUNGU WICARA DI UPT PELAYANAN SOSIAL TUNA RUNGU WICARA DAN LANSIA PEMATANG SIANTAR - Febrina Odelia M. Simanjorang (Welfare StatE, 2013)
One of the social problems faced by Indonesia at this time include disability issues . Disabled people also have the same rights and obligations in all aspects of life and livelihood , which are entitled to work in accordance with the type and degree of disability that is on them . Disabled people should be able to develop and improve the physical, mental and social so it is expected that the relevant able to work in accordance with the level of skills , education and skills possessed and in accordance with the interests and experiences , so as to achieve self-reliance in public life . One effort to empower people with disabilities conducted by the North Sumatra provincial government particularly for hearing impaired speech is the provision of skills training programs for persons with disabilities who conducted the hearing impaired speech in the Technical Implementation Unit ( UPT ) Social Services Speech and Deaf Elderly Siantar. This form of descriptive research study that examines issues of skills training programs for persons with disabilities deaf mute . This study aims to determine the effectiveness of skills training programs for persons with disabilities in UPT deaf mute Deaf Social Services Speech Siantar . The sample was deaf inmates social skills training speech which consists of 18 people who all serve the population. Data were collected using a questionnaire and analyzed using descriptive statistics . Indicators used to measure the effectiveness of the skills training programs is a reaction, learning, behavior and organizational impact to the respondents. To determine the level of effectiveness of skills training programs , measurement data using a Likert scale . The results concluded that the effectiveness of skills training programs for persons with disabilities in UPT deaf mute Deaf Talk Social Services and Seniors Siantar been effective with a value of 0.63 Likert scale . Respondents' reactions to the program is effective as much as 0.64 . Effective learning process as much as 0.62 respondents . Changes in respondent behavior as 0.65 . Impact of skills training programs for the respondents also effective as 0.62 . Respondents who follow vocational training and skills now have more confidence . Keywords : Effectiveness , Skills Training Program , Disabled , Deaf Talk .